Reducing the reliance on global value chains by strengthening backward linkages - Bamituni Etomi Abamu (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
This Perspective explores the consequences of the ECJ decision in the Xella case over the protection of EU security from threats linked to indirect FDI. While the judgement excludes them from the scope of the EU FDI Screening Regulation, this Perspective offers a solution to include them under its scope.
Keywords: 330